The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1177/0963689717720050
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Hepatocyte Microbeads for Clinical Transplantation

Abstract: Intraperitoneal transplantation of hepatocyte microbeads is an attractive option for the management of acute liver failure. Encapsulation of hepatocytes in alginate microbeads supports their function and prevents immune attack of the cells. Establishment of banked cryopreserved hepatocyte microbeads is important for emergency use. The aim of this study was to develop an optimized protocol for cryopreservation of hepatocyte microbeads for clinical transplantation using modified freezing solutions. Four freezing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Recently, novel methods for the cryopreservation of hepatocytes have been reported to improve the viability after freezing and thawing, i.e., alginate gel encapsulation [24,25], and vitrification [26]. Surprisingly, the combination of cryoprotective supplements such as anti-apoptotic pan-caspase inhibitor, iron chelator, and human serum albumin and alginate gel encapsulation increased albumin production of cryopreserved hepatocytes rather than freshly isolated hepatocytes [24]. The cryopreservation of a large mass of encapsulated hepatocytes has also been reported [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, novel methods for the cryopreservation of hepatocytes have been reported to improve the viability after freezing and thawing, i.e., alginate gel encapsulation [24,25], and vitrification [26]. Surprisingly, the combination of cryoprotective supplements such as anti-apoptotic pan-caspase inhibitor, iron chelator, and human serum albumin and alginate gel encapsulation increased albumin production of cryopreserved hepatocytes rather than freshly isolated hepatocytes [24]. The cryopreservation of a large mass of encapsulated hepatocytes has also been reported [25].…”
Section: Discussionmentioning
confidence: 99%
“…The technique has been proven successful in a rat model of acute liver injury (35), and has shown encouraging results when used in children with ALF (unpublished). Furthermore, a recent study has shown that alginate microbeads containing hepatocytes can be cryopreserved with some maintenance of hepatic functions after thawing, figuring the possibility of an off-the-shelf product available in an emergency setting typical of fulminant liver failure (86).…”
Section: Future Developmentsmentioning
confidence: 99%
“…One strategy involves the encapsulation of the donor cells in microbeads which provide an immune-protective coating while enabling the maintenance of necessary metabolic functions (75, 7982). This approach is more amenable to the management of acute liver failure and recent work establishing animal models and developing mechanisms to create banked, cryopreserved microbeads for emergency use are potential advancements (83, 84). Additional techniques used to evade the host immune system include tissue-engineering strategies whereby liver mass constructs are assembled ex vivo and then inserted (usually into the peritoneal cavity) to provide a functional support system (8587).…”
Section: Improving Transplanted Hepatocytes Engraftment and Repopulationmentioning
confidence: 99%